ICP27 mediates HSV RNA export by shuttling through a leucine-rich nuclear export signal and binding viral intronless RNAs through an RGG motif - Sandri-Goldin, Rozanne M. (Cold Spring Harbor Laboratory Press, 1998)
Infection of metazoan cells with some viruses alters the balance of cellular mRNA export to favor viral RNA export and to retain cellular transcripts in the nucleus. Here, evidence is presented to show that the herpes simplex virus 1 (HSV-1) essential regulatory protein ICP27, which inhibits host cell-splicing, resulting in the accumulation of unspliced transcripts in the nucleus, mediates RNA export of viral intronless mRNAs. ICP27 was shown to shuttle between the nucleus and cytoplasm through a leucine-rich nuclear export signal, which alone was able to direct the export of the heterologous green fluorescent protein. In vivo UV irradiation studies demonstrated that ICP27 could be crosslinked to poly(A)(+) RNA in the nucleus and the cytoplasm, supporting a role in export. Furthermore, the amount of hnRNP A1, which has been implicated in the export of cellular spliced mRNAs, that was bound to poly(A)(+) RNA in HSV-1-infected cells was reduced compared with uninfected cells. In addition, it was demonstrated that ICP27 bound seven intronless HSV-1 transcripts in both the nucleus and the cytoplasm, and export of these transcripts was diminished substantially during infection with an ICP27 null mutant virus. In contrast, ICP27 did not bind to two HSV-1 mRNAs that undergo splicing. Finally, binding of ICP27 to RNA in vivo required an arginine-glycine region that resembles an RGG box. These results indicate that ICP27 is an important viral export factor that promotes the transport of HSV-1 intronless RNAs.